The Quantitative and Qualitative Assessment of Groundwater in Karbala Governorate, Iraq - Abdul-Razzak, Mohammed Ibrahim; Al-Neif, Ayser Abdul-Aziz (European Journal of Applied Sciences, 2021)
Karbala governorate, however, neighborhood the western desert, which bounded by longitudes (43° 09’ 41" – 44° 18’ 56") and latitudes (32° 10’ 15" – 32° 50’ 15") with total area study of 4987 km2, represents part of sedimentary plain belongs to the unstable shelf and Salman zone belongs to the stable shelf. The main geological formations that exposed in the studied area represented by Al-Fatha Fn. (M. Miocene), Injana Fn. (U. Miocene), Dibdiba Fn. (Pliocene – pliestocene) and Quaternary Fn. (Pliestocene – Holocene). Two main underground reservoirs were distinguished based on the sedimentary facies and (four water reservoirs) as well. Quantitatively, the assessment was based on the climatic information (rainfall, temperature and humidity) for (39 years) for the period (1980 - 2019), so, by using Thornorite equation the water surplus was calculated representing the renewable storage of the unconfined aquifer which amounted to (110.9 * 106 m3/year), while the fixed storage for both systems (unconfined and confined) were calculated as (7.68 * 109 m3) and (6.16 * 109 m3) respectively, with total equivalent to (13.84 * 109 m3). While qualitatively, the assessment was based on utilizing the data bank information (151 wells) belongs to the general commission for ground water (2013) in addition to some available field data. The results reveal that there are some wells that are within the permissible limits to be used for drinking purposes, which can be used for municipal after conducting biological tests on them, although they should not be used for agriculture. In general, it can be said that most of the water from the wells in the study area is suitable for agricultural use, with the exception of small scattered areas.